2016
DOI: 10.1002/1873-3468.12088
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 channel regulates ox‐LDL‐induced proliferation and migration of vascular smooth muscle cells via MEKERK pathways

Abstract: Transient receptor potential melastatin 7 (TRPM7) plays a key role in the pathophysiological response of multiple cell types. However, the role of TRPM7 channels in ox-LDL-induced proliferation and migration of VSMC remains unclear. This study used the thoracic aorta VSMCs to explore the effects of ox-LDL on cell proliferation and migration and to investigate the underlying molecular mechanisms and signaling pathways. Data demonstrated that ox-LDL significantly increased TRPM7 activity, and induced VSMC prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
(58 reference statements)
1
24
0
Order By: Relevance
“…ERK is an important phosphorylase kinase that can widely activate downstream molecules and is involved in the regulation of cell function. A large number of studies have shown that ERK participates in many signaling pathways regulating proliferation in VSMCs . Therefore, ERK, as a mid‐downstream signal transduction molecule, may serve as a pivotal molecule for multiple proliferation regulatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…ERK is an important phosphorylase kinase that can widely activate downstream molecules and is involved in the regulation of cell function. A large number of studies have shown that ERK participates in many signaling pathways regulating proliferation in VSMCs . Therefore, ERK, as a mid‐downstream signal transduction molecule, may serve as a pivotal molecule for multiple proliferation regulatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To further understand the regulatory mechanisms of EMV, we examined the Mek/Erk pathway which comprise important proteins related with the migration of VSMC (Jeong et al, 2015; Lin et al, 2016). In this study, we found that EMV increased Mek1/2 and p-Erk1/2 in HBVSMC and blockade of the Mek1/2/Erk1/2 pathway inhibited the effect of EMV on promoting migration of HBVSMC.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that EMV promote migration of HBVSMC via activation of the Mek1/2/Erk1/2 pathway, thereby providing a probable underlying mechanism in the process of pro-atherosclerosis. The Mek-Erk pathway has been shown to be involved in VSMC proliferation and migration under an inflammatory environment (Lin et al, 2016). Nevertheless, whether it plays a role in VSMC apoptosis has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some biological processes contribute to the atherosclerotic plaque formation and progression, including smooth muscle cell migration and proliferation, macrophage foam cell formation, and altered expression of cytokines and growth factors (Pirillo et al, 2013). Ox-LDL significantly promotes VSMCs migration and proliferation in intimal area through activating the ERK1/2 signaling pathway transcription factors, which is a main feature of atherosclerotic lesions (Cutini and Massheimer, 2010; Lin et al, 2016; Yang et al, 2001). In macrophages, ox-LDL is capable of targeting several scavenger receptors and induces production of proinflammatory cytokines such as tumor necrosis factor (TNF)-α, oxidative stress, and enhances chemotaxis (Sun et al, 2009).…”
Section: Introductionmentioning
confidence: 99%